Sports tourism in Zimbabwe: an analysis - Hlupo, Emmanuel N. (Midlands State University, 2017)
There has been an increasing concern by the tourism and sports stakeholders to develop sports tourism in Zimbabwe. There are fears escalating that the organisations and the country lose a lot of potential benefits because of failure to fully recognise and give adequate attention to sports tourism which is tourism multibillion niche. This research therefore sought to undertake an analysis of sports tourism in Zimbabwe, realising were the country stand as compared to other nations that participate in the tourism sub-sector. As an objective the study sought to reveal the state of sports tourism in Zimbabwe. The research also identified the benefits that sports tourism brings to a destination partaking in it. The study entailed examination of the challenges that Zimbabwe is facing in the quest of the full development of sports tourism. The research also produced feasible recommendations on how to enhance sports tourism in Zimbabwe. It was identified that the state and extent of the opportunities that sports tourism bring to the development of Zimbabwe was not well known and documented, this research sought to close the gap. The researcher selected 5 organisations and 2 ministries in both the sports and tourism sectors as research units that fairly represented all the direct stakeholders in sports tourism. These were Ministry of Tourism and Hospitality, Ministry of Sports, Arts and Culture, Zimbabwe Tourism Authority, Hospitality Association of Zimbabwe, Zimbabwe Rugby Union, Zimbabwe Cricket, Zimbabwe Football Association and Zimbabwe Sports Commission. In this study the researcher used the descriptive research design to collect, analyze and present data in an attempt to provide a flawless picture on the current state of sports tourism and challenges it faced in Zimbabwe. Open-ended questionnaires and direct interviews were used to collect primary data to determine opinions, attitudes, preferences and expectations of these targeted respondents. Qualitative and quantitative data were both collected and analyzed by the researcher. Expert sampling was mostly used in the research whereby respondents were selected based on their known or demonstrable experience and proficiency in the area of sports and tourism. From the research it was found out that the state of the sports tourism facilities and capacity were not adequate as stated by 90% of the respondents. 90% of the respondents also stated that most of the sports events in the country are staged in Harare. It was also found out that sporting organisations had no sports tourism strategy; this reflected that the state of sports tourism in Zimbabwe was in an intensive care unit. The organisations were recommended to devise a sports tourism strategy and come up with ways to upgrade the existing the facilities to meet international standards rather than being ambitious to build new facilities and also to create joint marketing initiatives with other stakeholders in sports tourism. The researcher suggests that future researchers should investigate on ways to avoid the uneven distribution of sports tourism in Zimbabwe and also they should look at the potential of sports tourism to create loyalty among tourists who visit the country.